Tourism towards economic development in Malaysia / Aziman Jalaludin - Jalaludin, Aziman (2012)
Tourism can be considered as third major contribution to economic development in Malaysia. This study examines the tourism sectors effect toward economic development in Malaysia. The data used based on times series data over the period 2000:Q1 until 2011 :Q4. This study use Augumented Dickey-Fuller (ADF) Test to test stationarity of the variables, Johansen Cointegration Test and Granger Causality Test to ascertain the direction of causality between variables.